'Where is the space for continuum?' Gyms and the visceral "stickiness" of binary gender. Issue 4 (4th July 2021) - Coen, Stephanie E.; Davidson, Joyce; Rosenberg, Mark W.
ABSTRACT: This paper develops a visceral feminist geography of the gym to expand our understanding of how everyday physical activity environments are implicated in the gendered context of physical activity. The gender gap in physical activity is well-documented, with women around the world less likely than men to meet the minimum physical activity recommendations for health. Fitness gyms are popular venues for physical activity, but they are not necessarily inclusive places. Through a reflexive thematic analysis of interview and journaling data with 52 Canadian women and men gym users, we identify five visceral domains through which the gym enacts gender boundaries: the imaginary, bodily haptics, the soundscape, visual fields, and material "stuff". Each of these revealed a series of gendered dichotomies that, taken together, contribute to an overarching gender binary of unbounded masculinity and bounded femininity. We argue that these "visceralities" matter because the gym as an institution comes to codify gender differences in ways that perpetuate possibilities for practising physical activity as bifurcated ways of doing gender. One of our key findings is how women's participation in the gym was underwritten by material expense and bodily preparatory practices that extend far beyond the gym into the geographies of their daily lives. Physical activity interventions that do not account for the multisensorial features of place may miss opportunities to reduce gendered inequities.